Indwelling Pleural Catheter in Recurrent Pleural Effusion Due To Congestive Heart Failure: A Case Report - Saputra, Tetra Arya; Wibowo, Adityo (Jurnal Ilmu Kedokteran dan Kesehatan, 2025)
Pleural effusion commonly appears in congestive heart failure (CHF), caused by raised pulmonary capillary pressure and impaired lymphatic drainage, often resulting in respiratory distress and reduced quality of life. This case report presents the use of an indwelling pleural catheter (IPC) for recurrent pleural effusion in CHF unresponsive to standard therapy. A 42-year-old man with acute decompensated CHF and bilateral pleural effusions presented with worsened dyspnea. Initial thoracentesis and diuretic therapy failed to resolve the effusion, leading to IPC placement for ongoing drainage. IPC insertion resulted in marked symptom improvement, effective fluid management, and shorter hospital stay. The patient was able to continue outpatient care and experienced no major complications. This case demonstrates that IPCs can provide safe and effective symptom control in CHF-related pleural effusions when conventional treatment is inadequate. Individualized strategies, including the use of IPC, may enhance quality of life and reduce hospitalizations in patients with effusions caused by heart failure.